2016
DOI: 10.1530/rep-16-0047
|View full text |Cite
|
Sign up to set email alerts
|

Interleukins, interferons, and establishment of pregnancy in pigs

Abstract: Early pregnancy in mammals requires complex and highly orchestrated cellular and molecular interactions between specialized cells within the endometrium and the conceptus. Proinflammatory cytokines are small signaling proteins released by leukocytes that augment innate and adaptive immune responses. They are also released by the mammalian trophectoderm as the conceptus apposes the uterine surface for implantation. On approximately day 12 of development in pigs, the conceptus undergoes a rapid morphological tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
47
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 86 publications
1
47
0
2
Order By: Relevance
“…Additionally, at D18 of pregnancy, we found a clear increase of the pro-inflammatory interleukin IL-1β in the C+ group compared to non-pregnant sows. This pro-inflammatory interleukin and its signaling system are expressed in the porcine endometrium and conceptuses during the peri-implantation period [39][40][41] inducing increases of the MAPK and NFKB activities in the endometrium [42], which stimulates the expression of genes involved in immune modulation, cell adhesion, and angiogenesis [17,43]. Immediately following implantation, IL-1β expression rapidly declines and the uterine content of IL-1β slowly decreases over the next few days and returns to pre-elongation concentrations [39], which is in accordance with our results at D24 of pregnancy where endometrial IL-1β concentrations tended to decrease in AI-pregnant sows compared to the non-pregnant controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, at D18 of pregnancy, we found a clear increase of the pro-inflammatory interleukin IL-1β in the C+ group compared to non-pregnant sows. This pro-inflammatory interleukin and its signaling system are expressed in the porcine endometrium and conceptuses during the peri-implantation period [39][40][41] inducing increases of the MAPK and NFKB activities in the endometrium [42], which stimulates the expression of genes involved in immune modulation, cell adhesion, and angiogenesis [17,43]. Immediately following implantation, IL-1β expression rapidly declines and the uterine content of IL-1β slowly decreases over the next few days and returns to pre-elongation concentrations [39], which is in accordance with our results at D24 of pregnancy where endometrial IL-1β concentrations tended to decrease in AI-pregnant sows compared to the non-pregnant controls.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the fact that in porcine, conceptus estrogen declines after their elongation to initiate a second increase, sustained during the period of uterine attachment (days 18 to 25 of pregnancy) [44]. Since IL-1β is a potent stimulator of aromatase activity and of subsequent estrogen synthesis [43], we hereby hypothesize that placental IL-1β production is increased in ET sows in an attempt to counteract the lack of estrogen signaling from the non-rejected allogeneic embryos remaining in utero. Moreover, allogeneic placentae also showed a higher expression of IL-1α compared to C+ conceptuses at D24 of pregnancy, which has been shown to negatively impact cell growth [45], suggesting that the development of the allogeneic embryos may be delayed in comparison with hemi-allogeneic conceptuses.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine family members, such as interleukins and interferons, are known to function in porcine pregnancy [62,63]. In this study, we identified common DEGs between Meishan and Duroc at both GD49 and GD72 that are involved in the regulation of type I interferon signaling pathway (IFI6, IFIT3, IFNA4, MX1, ISG15, and USP18).…”
Section: Discussionmentioning
confidence: 95%
“…IRF1 regulates expression of target genes by binding to the interferon-stimulated response element. Interferon activity is known to regulate reproductive biology, more specifically early pregnancy stages (Mathew et al, 2016, Wiltbank et al, 2016. IRF1 has also been shown to play a role in regulating post-translational modifications to tumour suppressor protein p53 (Dornan et al, 2004).…”
Section: Discussionmentioning
confidence: 99%